Maharshi Dayānanda dvārā pratipādita rājya-vyavasthā - Prashant Kumar, 1937- (Govindarāma Hāsānanda, 1975)
On the political system as expressed by Swami Dayananda Sarasvati, 1824-1883, founder of the Arya Samaj, Hindu reform movement.